The influence of food motives on attitude: a study of genetically modified organism food in Malaysia - Uddin, Mohi; Jan, Muhammad Tahir; Maulan, Suharni (2025)
The influence of food motives on Malaysian consumers’ attitudes towards genetically modified (GMO) foods is explored in this study, specifically to investigate whether motivations can be explained by four dimensions: knowledge, risk perception, technology orientation and labelling. A structured questionnaire was used to collect 337 usable responses. Structural Equation Modelling (SEM) was employed to test the hypothesised relationship. The findings reveal that food motive has a significantly positive influence on consumer attitude toward GMO food. The results of the study emphasise the necessity to improve consumers’ knowledge, risk perceptions, and to increase labelling transparency to increase the consumers’ support for GMO food products in Malaysia. The findings offer policy implications for policymakers, advertisers, and stakeholders involved in GMO food promotion and regulation.